Increased Number of Functional Tics Seen in Danish Adolescents during the COVID-19 Pandemic - Okkels, Kirstine Birkebæk; Skov, Liselotte; Klansø, Susanne; Aaslet, Lone; Grejsen, Judy; Reenberg, Annika; Sørensen, Camilla Birgitte; Debes, Nanette Marinette Monique Mol (Neuropediatrics, 2023)
Background Global increase in functional tics in adolescents has been observed. Differentiating functional from classic tics is important since pathophysiology and treatment differ. We investigated possible triggers for development of functional tics and discuss the possible role of the coronavirus disease 2019 (COVID-19) pandemic and social media exposure in cases of functional tics seen during this period. Moreover, the treatment, and its efficacy is discussed.Methods Medical records of 28 Danish adolescents diagnosed with functional tics at the National Tourette Clinic, Department of Pediatrics, Herlev University Hospital, Denmark, from May 2020 to June 2021 have been retrospectively reviewed. Descriptive statistical analyses were used to analyze the data.Main Findings A total of 28 patients diagnosed with functional tics were included, 96.4% girls and 3.6% boys, mean age 14.4 years. Tic phenomenology differed from classic tics with more complex tics and no rostrocaudal progression. Note that 69.2% reported harmful tics. Also, 78.6% had trauma/precipitating event and 40% denounced lockdown related to the COVID-19 pandemic as trigger, both prior to onset of functional tics. Note that 60.7% reported psychiatric symptoms/diagnoses, 42.9% had a first-degree family member with psychiatric symptoms/diagnoses, and 96.4% were exposed to tics on social media prior to onset. Treatment consisted of psychoeducation, elements from cognitive behavioral therapy, and focus on psychiatric symptoms. All patients responded to the treatment.Conclusion The vulnerability of the adolescents is characteristic. Treatment strategy has shown immediate positive effect. Consequences of the COVID-19 pandemic in combination with exposure to tics on social media could be part of the cause for the increase in number of functional tics.
Keywords: functional tics; functional movement disorder; COVID-19; social media; adolescents; Tourette syndrome